Changing Employee Registration Numbers as a Mechanism to Avoid Permanent Employment Status: A Normative and Empirical Legal Analysis of Indonesia’s Manufacturing Sector During the Transition Period of Labor Law (2017–2024) (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the practice of changing Employee Registration Numbers as a mechanism that may obscure employment continuity and affect access to permanent employment status in Indonesia’s manufacturing sector during the labor law transition period from 2017 to 2024. An explanatory mixed methods design was employed by integrating normative legal analysis with empirical survey research. The normative component analyzed major labor regulations and relevant legal scholarship, while the empirical component involved manufacturing workers who had experienced repeated fixed term employment arrangements. Documentary evidence and questionnaire data were used to assess employment continuity, legal literacy, and perceptions of contractual rights. The findings indicate that Employee Registration Number replacement frequently coincided with uninterrupted work relationships despite administrative changes. Survey results revealed limited worker understanding of fixed term and permanent employment regulations, particularly regarding the legal implications of administrative identity changes. The study further demonstrates that legal uncertainty during regulatory transition, combined with low legal literacy and weak institutional oversight, contributed to the persistence of the practice. These findings highlight the importance of strengthening labor governance, legal awareness, and enforcement mechanisms to improve employment protection and regulatory effectiveness.